Constrained Cyclopeptides: Biaryl Formation through Pd‐Catalyzed C−H Activation in Peptides—Structural Control of the Cyclization vs. Cyclodimerization Outcome. Issue 37 (4th August 2016) - Mendive‐Tapia, Lorena; Bertran, Alexandra; García, Jesús; Acosta, Gerardo; Albericio, Fernando; Lavilla, Rodolfo
Abstract: A series of short tryptophan‐phenylalanine peptides containing an iodo substituent on the phenyl ring was subjected to Pd‐catalyzed CH activation reactions to give the corresponding aryl‐indole coupled products. Two types of adducts were generated: cyclomonomer and cyclodimeric peptides; no evidence of oligo‐ or polymerization products was detected. Contrary to standard peptide macrocyclizations, the factors controlling the fate of the reaction are the number of amino acids between the aromatic residues and the regiochemistry of the parent iodo derivative, independent of both the concentration and the cyclization mode. The method is general and allows access to novel biaryl peptidic topologies, which have been fully characterized. Abstract : Cyclization or cyclotrimerization : A systematic study of the macrocyclization of a series of biaryl peptides through a Pd‐catalyzed C−H activation process reveals the key structural parameters that determine the course of the process and can serve as a guide to predict the fate of these systems (see figure).